Table of Content - - (Journal of Humanities & Social Sciences, 2025)
:Table of Content • General social aspects in Baghdad through the book ’Nishwar AI-Muhadara’ by AI-Tanukhi Asst-Lecturer. Ahmad Taleb Malouh, Asst-Prof. Hamid Karimipour • The Maturation of Developmental Concepts in Islamic Thought and Its Impact on Guiding Human Action: The Model of Justice from Theological Belief to Moral Education Dr. Fazry Hamza • Ibn Rushd and his intellectual and philosophical role: A study of his intellectual influences in Europe and the Western opinion of him Asst-Lecturer. Zainab Nasser Abdul-Hussein Al-Azirjawi, Asst-Prof. Nour Al-Din Nemati • The Role of Digital Communication in Promoting Civic Participation – Moroccan platform I share a model – Dr. Filali S. Zineb • The Impact of Social and Cultural Factors on the Effectiveness of Tourism Management in Major Projects: A Human-Centered Perspective Eng. Ashraf Fawzy Al-Jindi • Reception Dynamics and the Theme of Human Fall in Absurdist Literature: An Interactive Reading of Three Short Stories by Friedrich Dürrenmatt" Dr. Hani Khamis Hamad • An Exploration of Morpho-Syntactic Elements of Block Language in Journalistic Discourse Mr. Omar Hazim Yaseen